Memahami Kepuasan Pelanggan terhadap Pelayanan Hotel: Suatu Tinjauan Pustaka Sistematis - Rina Suprina; Heny Hendrayati; Vanessa Gaffar; Ratih Hurriyati (Jurnal Manajemen dan Organisasi, 2022)
Customer satisfaction is an important factor in the management of the hospitality industry because satisfied customers tend to revisit and provide recommendations to others so that in the end it will provide benefits for the hotel. This paper aims to review the literature related to hotel guest satisfaction. To obtain literature data, the Publish or Perish software was used and the Google Scholar and Scopus databases in Publish or Publish were selected. The title word used is "customer satisfaction hotel". The results of the initial data search were then rechecked by removing documents that were considered less relevant to the keywords/titles discussed. The final search results using the Google Scholar and Scopus databases were then stored in the Mendeley reference manager. Using Mendeley and Publish or Perish software, data on the 10 most cited articles and data on the 8 best journals were obtained. Furthermore, VOSviewer software was used to obtain network visualization and cluster data consisting of items that appear in each cluster. This study provides an overview for further research on hotel customer satisfaction related to factors that need to be investigated further. The results of this literature review will also be useful for hotel managers in an effort to increase customer satisfaction by considering factors related to customer satisfaction.